Connectivity, land use, and fish presence influence smooth newt (Lissotriton vulgaris) occurrence and abundance in an urban landscape - Vehkaoja, Mia; Thompson, Stella M. A.; Niemi, Milla; Väänänen, Veli-Matti (Frontiers in Ecology and Evolution, 2023)
Urban areas are challenging environments for wetland species with complex habitat requirements and life cycles. However, even semiaquatic species, representing such complex wetland groups, can be provided with adequate conditions through thorough understanding of their habitat requirements coupled with comprehensive wetland management. We studied the occurrence and abundance of the smooth newt (Lissotriton vulgaris), a widely distributed amphibian, in an urban landscape in metropolitan Helsinki, Finland. We classified 50 randomly selected urban wetlands based on their connectivity by applying isolation scores counted using principal component analysis (PCA) and measured the occurrence and abundance of smooth newts in these locations. Our analyses showed well-connected wetland sites to differ significantly in smooth newt occurrence from both isolated and partially connected sites. Additionally, smooth newt abundance in well-connected wetlands differed from isolated sites. A PCA model with residential buildings (negative effect) and aquatic vegetation (positive effect) best explained smooth newt occurrence and total and male abundance, and female newt occurrence was best explained by a model also incorporating forest and natural open areas. Predation pressure by fish negatively influenced both smooth newt occurrence and abundance. Tighter networks of constructed wetlands and stricter management guidelines for urban wetland planning and fish community management could increase the suitable habitat for smooth newts in urban landscapes. Managing such areas for the common smooth newt offers potential broad benefits to the conservation of other semiaquatic amphibians and reptiles in urban wetlands and to urban wetland biodiversity in general. Our results show that smooth newt presence may indicate sustained 2 This is a provisional file, not the final typeset article wetland connectivity in an urban landscape and could even be used to signal successful urban planning.